Low-order harmonics cancellation for three-phase grid-connected inverters using a band pass filter - An, Sang Won; Kim, Seok Min; Cho, Sungjoon; Lee, Kyo Beum (Transactions of the Korean Institute of Electrical Engineers, 2020)
This paper proposes a novel control method to effectively reduce the low-order harmonics contained in the grid current. When different kinds of loads or non-linear loads are connected to the Point of Common Coupling(PCC), harmonics are generated in the grid voltage, which causes output current distortion of inverter. This current distortion causes reduced efficiency and resonance of the power converter. In general, to reduce the current distortion, a low-order harmonic cancellation technique is used using proportional-integral control and low-pass filter. This method cannot effectively remove the harmonic component of the grid current due to the effect of the fundamental wave. In this paper, an effective harmonic control method is proposed, in which the effects by fundamental wave components have been removed. Simulation and experimental results verify the effectiveness and validity of proposed method.
Keywords: Current distortion; Fundamental wave; Grid connected inverters; Harmonic components; Low order harmonics; Point of common coupling; Proportional-integral control; Three-phase grid connected inverters; Band pass filter; Fundamental wave; Grid-connected inverter; Low-order harmonics